2021
DOI: 10.1126/sciadv.abj9141
|View full text |Cite
|
Sign up to set email alerts
|

MLL4 mediates differentiation and tumor suppression through ferroptosis

Abstract: This study reveals how epigenetic errors drive skin cancer initiation via altered cell fate and impaired ferroptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 58 publications
1
38
2
Order By: Relevance
“…We speculated that some of the epigenetic factors may possess essential roles in the regulation of both tumor aggressive behaviors and tumor immunity, and thus can favor both tumor development and suppression. In accordance with our assumption, prior studies have found conditional deletion of Mll4 confers growth advantages and causes blockade of differentiation program and ferroptosis suppression, thus synergizing with genetic lesions of additional genes to promote tumor development in multiple mouse tissues 34 , 35 , 55 , 73 , 74 . We and others found that Mll4 ablation elevates the expression of multiple chemokines, including CXCL9 and CXCL10, and the increased levels of molecules responsible for antigen processing and presentation 75 , which augments CD8 + T-cell-mediated anti-tumor immune response to suppress tumor development 16 , 49 .…”
Section: Discussionsupporting
confidence: 90%
“…We speculated that some of the epigenetic factors may possess essential roles in the regulation of both tumor aggressive behaviors and tumor immunity, and thus can favor both tumor development and suppression. In accordance with our assumption, prior studies have found conditional deletion of Mll4 confers growth advantages and causes blockade of differentiation program and ferroptosis suppression, thus synergizing with genetic lesions of additional genes to promote tumor development in multiple mouse tissues 34 , 35 , 55 , 73 , 74 . We and others found that Mll4 ablation elevates the expression of multiple chemokines, including CXCL9 and CXCL10, and the increased levels of molecules responsible for antigen processing and presentation 75 , which augments CD8 + T-cell-mediated anti-tumor immune response to suppress tumor development 16 , 49 .…”
Section: Discussionsupporting
confidence: 90%
“…This variant causes GSH and CoA accumulation (Leu et al, 2019), as well as iron accumulation and increased risk of infection, but resistance to the malaria toxin hemozoin, perhaps explaining its selection in regions with a high risk for malarial infection (Singh et al, 2020). Knockout in mice of the epigenetic regulator MLL4, which is commonly altered in cutaneous squamous cell carcinomas in the skin, caused the development of pre-cancerous skin lesions (Egolf et al, 2021). The loss of MLL4 in the skin of these mice drives transcriptional changes that suppress ferroptosis, including the increased expression of SLC7A11, GPX4, and stearoyl-CoA desaturase 1 (SCD1), all of which drive resistance to ferroptosis, and loss of expression of the lipoxygenases ALOX12, ALOX12B, and ALOXE3; as noted above, these lipoxygenases promote ferroptosis in some contexts (Figure 4).…”
Section: Tumor Suppression and Immune Functionsmentioning
confidence: 99%
“…In liver and pancreas cancer models, UTX can control the expression of negative regulators of mTOR such as DEPTOR , and its disruption prevents their transcription and facilitates tumorigenesis through increased mTORC1 activity (Revia et al, 2021). Additionally, while the mechanisms of MLL4 activity in liver cancer have not been examined, studies suggest that MLL4 suppresses skin carcinogenesis by promoting lineage stability and ferroptosis independently of MLL3 (Egolf et al, 2021). Our study demonstrates that MLL3 is both necessary and sufficient for efficient transcriptional activation of the CDKN2A locus that drives oncogene-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%